Social Support in Career Women Who Lost Their Partners In Samarinda City - Farida Nur Rahmwati; Maulidya Shalzabila Indah; Ahmad Nur Faizi; Dian Dwi Nur Rahmah (Politeknik Negeri Bengkalis, 2022)
Loss of a life partner can occur because of a divorce, either a life divorce or a dead divorce. Losing a life partner can be quite a traumatic event in a person's life as well as in a career woman. Career women who lose their partners will carry out increasingly arduous tasks, namely becoming the head and backbone of the family, as well as being a mother and father to their children. Thus, career women who lose their partners need social support from those around them. This study is phenomenological qualitative research that aims to find out the picture of social support in career women who have lost their partners in Samarinda City. The subjects in this study were 4 people who had been selected according to the specified characteristics, namely career women who were married and had children, as well as lost their partners. The results of this study showed that the social support obtained by subjects who lost their partners was in the form of emotional support in the form of encouragement, instrumental both in the form of money and services, information, and friendships provided from people around them such as family, friends, and co-workers where different dynamics emerged obtained in career women who lost their partners due to death where they remained supported by the families of the subjects' ex-husbands